Sustainable intensification in eastern gangetic plains of South Asia via conservation agriculture for energy, water and food security under climate smart management system - Gathala, Mahesh Kumar; Mahdi, S. Sheraz; Jan, Rukhsana; Wani, Owais W.; Parthiban, M. (Springer, 2022)
Rice cultivation in the South Asian region of Eastern Gangetic Plains (EGP) is running out of water, labour, low productivity and profitability. In addition, this system of crop production often ignores CO2-equivalent greenhouse-gas emissions, which are often rather significant. Although a dominant food-producing region in Asia is becoming poor in crop production, crop management approaches based on conservation agriculture-based sustainable intensification (CASI) increase the crop yields and improve profitability while lowering the water, energy and labour requirements, as well as greenhouse-gas emissions. The use of CASI approaches in EGP region villages and districts enhances crop diversification and intensifies their production. It also facilitates employment opportunities and micro entrepreneurship in rural areas. In on-farm experiments traditional and improved approaches in rice-based cropping systems were compared. We discovered that CASI management approaches increased the crop yields by 10%, reduced labour demand by 50% and increased water and energy productivity by 19% and 26% respectively. Overall, these findings showed that using CASI lowered crop production costs by up to 22% and raised gross margins by 12–32% compared with traditional methods. CASI management also resulted in CO2-equivalent emissions that were between 10% and 17% lower than those with traditional management. Initially, this principal research was collaborated on with farmer support groups for further extension. To encourage CASI adoption and out-scaling on a scale outside of research domains, an actively supporting policy environment was required.